The Effect of the iSpring - Assisted PBL Model on Students' Literacy HOTS on Reaction Rate - Seli Cornelya Marantara Tambunan; Marini Damanik (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
Every student is enforced to master scientific literacy in everyday life because this literacy is relevant to students' ability to related issues about science and their ideas as citizens. This research aims to analyze students' HOTS literacy scores using the PBL model with the assistance of iSpring Presenter media on reaction rate material to the hypothesized value of 70 and to present the aspects of HOTS literacy that are experiencing the most progress. This research used a One-Group Pretest-Posttest design. Based on test validation, 20 questions out of 22 valid questions were used (12 questions on the C4 aspect of reasoning, 6 questions on the C5 aspect of reasoning, and 2 questions on the C6 aspect of reasoning). Data analysis shows that the N-Gain value meets the high criteria, namely 70.03%. Hypothesis test analysis shows that ha is accepted or exceeds what was hypothesized (70), the tvalue is 6.96, and the ttable is 2.03 which is outside the ho acceptance area with a two-party test. As well as the results of the analysis of the HOTS aspect of literacy that was most developed in this research was the C5 aspect of reasoning with a percentage of 73.44%.